Components of Cancer Metabolism and Therapeutic Interventions - Singleterry, John (2014)
All forms of life share a common indispensible need of energy. The requirement of energy is necessary for an organism not only to survive but also to thrive. The metabolic activities in normal cells rely predominately on mitochondrial oxidative phophorylation for energy generation in the form of ATP. On the contrary, cancer cells predominately rely on glycolysis rather than oxidative phosphorylation. It is long believed that an impairment of mitochondrial oxidative phosphorylation is the cause of this glycolytic phenotype observed in cancers. However, studies in cancer metabolism have revealed that mitochondrial function in many cancers is intact. It has also been observed that cancers utilize various forms of metabolism. The various metabolic phenotypes are employed by cancer cells have a common purpose, to balance macromolecular biosynthesis and sufficient ATP production in order to support the rapid proliferation rate characteristic of these aberrant cells. These metabolic pathways are attractive targets for possible therapeutic interventions and currently research is underway to meet this end. More importantly, normal cells have essentially the same metabolic requirements as cancer cells so finding an approach to target these metabolic pathways without incurring detrimental effects on normal tissues remain the challenge.